(untitled) (World Bulletin of Public Health, 2023)
The purpose of the study was to assess the state of the morphological structure of platelets in women with recurrent miscarriage in the presence of antiphospholipid antibodies. The study involved 78 women aged 18 to 26 years, 24 of them (Group 1) were patients with an incipient miscarriage, in the presence of antiphospholipid antibodies and retained their pregnancy. In 54 patients (Group 2) with aborted pregnancy. The morphology and activity of platelets were studied. It has been established that in women with miscarriage in the presence of antiphospholipid antibodies, there are significant changes in the morphology of platelets and a consistently high activity of platelets.